Familiarity with occupational therapy among secondary school youths planning to pursue medical studies in Poland - Aneta Bac; Aleksandra Kulis; Edyta Janus; Paulina Aleksander-Szymanowicz; Wojciech Dobrowolski; Katarzyna Filar-Mierzwa (Health Promotion & Physical Activity, 2021)
Introduction: Poland has been a member of the European Union for 17 years; however, the societal view of occupational therapy is limited and different from that in the other countries of the European Union or the world. The aim of the study was to determine the familiarity with occupational therapy among secondary school students who are the future candidates for higher medical studies and potential members of interdisciplinary teams. Material and methods: The study encompassed 1865 randomly selected secondary school students (1212 women and 653 men). The research was conducted with the use of a questionnaire with 18 multiple choice questions. Results: The majority of the respondents admitted that they were familiar with terms occupational therapy and occupational therapist but the terms were unknown to 416 persons. 1414 respondents indicated that in their opinion occupational therapist can work in rehabilitation centres. The highest number of the respondents indicated children with inborn defects, such as Down syndrome (1261 persons) in the groups of people that an occupational therapist may work with. Conclusions: The presented results indicate a relatively low level of knowledge of the respondents about occupational therapy, which reflects the overall situation of the profession in Poland.